An Experimental Study of Natural Convection Heat Transfer from a Horizontal and Slightly Inclined Plate-Fin Heat Sink - Khalaf, Almustafa A.; Sultan, Hussien S.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2023)
The steady-state natural convection from heat sink fin arrays was studied on horizontal, vertical, and inclined heat sinks. Under natural convection, horizontal and vertical heat sinks with parallel fins were tested by considering radiation heat transfer. The experiments were conducted with power inputs ranging from 60 W to 455 W in order to obtain different temperatures. According to the result, when heat input increases, the heat transfer coefficient increases by 38 %, 40.78 % for horizontal and vertical respectively. For horizontal and vertical cases, new correlations have been presented to calculate the Nusselt number influenced by the Rayleigh number. For the incline case, the effect of buoyancy force was studied by changing the inclination angles at 0, 30, 45, and 60 degrees from vertical position. According to comparisons between vertical and incline cases, Nusselt number and heat transfer coefficient were most improved at 30 degrees by 6 %.